2014
DOI: 10.1111/tpj.12456
|View full text |Cite
|
Sign up to set email alerts
|

The vacuolar calcium sensors CBL2 and CBL3 affect seed size and embryonic development in Arabidopsis thaliana

Abstract: SUMMARYStimulus-specific calcium (Ca 2+ ) signals have crucial functions in developmental processes in many organisms, and are deciphered by various Ca 2+ -binding proteins. In Arabidopsis thaliana, a signaling network consisting of calcineurin B-like (CBL) protein calcium sensors and CBL-interacting protein kinases (CIPKs) has been shown to fulfil pivotal functions at the plasma membrane in regulating ion fluxes and abiotic stress responses. However, the role of tonoplast-localized CBL proteins and espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 50 publications
1
49
0
Order By: Relevance
“…Extensive studies from various independent research groups indicated that the CBL family members target only a group of serine/threonine protein kinases called CIPKs [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Until recently, therefore, it had been strongly believed that CBLs do not possess the target diversity exhibited by other sensor relays, CaMs and CMLs.…”
Section: Introductionmentioning
confidence: 97%
“…Extensive studies from various independent research groups indicated that the CBL family members target only a group of serine/threonine protein kinases called CIPKs [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Until recently, therefore, it had been strongly believed that CBLs do not possess the target diversity exhibited by other sensor relays, CaMs and CMLs.…”
Section: Introductionmentioning
confidence: 97%
“…More recent work has uncovered that four of the ten CBLs are localized at the tonoplast membrane [17], and reverse genetic analyses of the calcium sensors CBL2 and CBL3 mutants have uncovered their function in regulating cellular ion homeostasis and their essential role for Arabidopsis pollen, seed and early embryonal development [18][19][20]. Subsequent studies of CIPK quadruple mutants identified CIPK3/ 9/23/26 as the CBL2/3 interacting kinases functioning in regulating cellular magnesium homeostasis [21,22].…”
mentioning
confidence: 99%
“…(Arabidopsis thaliana) mutants (Zhu, 2002;Cheong et al, 2003Cheong et al, , 2007Kim et al, 2003;Pandey et al, 2004D'Angelo et al, 2006;Qin et al, 2008;Tripathi et al, 2009;Held et al, 2011;Tang et al, 2012;Drerup et al, 2013;Eckert et al, 2014). A few CIPKs have also been functionally characterized by gain-of-function approach in crop plants such as rice (Oryza sativa), pea (Pisum sativum), and maize (Zea mays) and were found to be involved in osmotic stress responses (Mahajan et al, 2006;Xiang et al, 2007;Yang et al, 2008;Tripathi et al, 2009;Zhao et al, 2009;Cuéllar et al, 2010).…”
mentioning
confidence: 99%